Peningkatan Pengetahuan Perpajakan untuk Mewujudkan Generasi Milenial Sadar Pajak di SMA Negeri 1 Pangkah Kabupaten Tegal - Syah, Asrofi Langgeng Noerman; Hasan, Imam; Fauzi, Arief Zul; Hanum, Naila (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
The community service program carried out at SMA N 1 Pangkah, Tegal Regency aims to increase knowledge of taxation in realizing a tax-aware millennial generation at SMA N 1 Pangkah, Tegal Regency so that it can provide an understanding to the younger generation about the importance of taxes for all components of the nation. The object of this Community Service Program are the students of SMA N 1 Pangkah, Tegal Regency. The solution provided is in the form of providing material on the basics of taxation, types of taxes, taxes as a citizen's obligation, taxes as an embodiment of the Pancasila precepts and defending the country as well as material on the importance of the tax-aware millennial generation. The result of this dedication is that students gain an adequate understanding of the basic knowledge of taxation and the importance of taxes for the state so that one day they can become tax-aware millennial generations.